WORLD HEALTH DAY-DIABETES, A GROWING MENACE - Sofia Shehzad (Gandhara University, 2016)
World Health day, celebrated each year on 7th of April is all about creating awareness regarding health issues confronting the global population. The theme this year is Diabetes - a metabolic disorder of menacing proportion. There are a host of misconceptions and lack of understanding amongst the general public regards its exact etiology, prevention, control and socio-economic impact. As of 2015 the prevalence of the disease worldwide is estimated around 415 million affectees1. This number is expected to rise to 592 million by 2035 2. The incidence and resultant mortality secondary to this epidemic is on the rise in low and middle economy countries such as Pakistan, with the disease expected to be the 7th leading cause of death by 2030 3 . Diabetes occurs when the pancreas loses its ability to produce the required insulin or the body fails to utilize the later resulting in raised blood sugar levels 4. As a consequence, malfunctioning of various organ systems ensues and various life threatening illnesses including heart attacks, strokes, nerve damage, kidney failure, blindness, impotence and infections takes a toll on the patient's health. Broadly it is classified into 3 types - Type I or Insulin dependent diabetes mellitus also referred to as 'juvenile diabetes' in which the production of insulin is affected - Type II or Non insulin dependent diabetes mellitus characterized by insulin resistance, and having a strong correlation with increased body weight and lack of exercise 5. It is also called `adult onset 'diabetes'. - Gestational diabetes affecting pregnant women with no past history of the disease, usually in the 2Ild or 3rd trimester 6. The disease usually manifests with the symptoms of frequent urination, thirst and hunger. Once a diagnosis is made based on Blood sugar estimation and monitoring levels of glaciated hemoglobin - HbAl c, management ensues directed at achieving optimum level of blood glucose and avoiding systemic complications. This goal is achieved by introducing life style changes from a sedentary to more active and less stressful way of living, supplemented with a balanced diet and regular exercise. This is especially helpful in Type II DM. Treatment is offered by means of Oral hypoglycemic or injectable insulin as guided by the physician/endocrinologist. More recently bariatric Surgery has shown considerable promise as an effective measure to control blood sugar levels.7 This year the main objective of observing the world health day is to enhance awareness about prevention, care and surveillance of this disease. This will form the basis for launching the first ever global report on Diabetes. The core functions of WHO in this regard are as follows: - To frame internationally acceptable standards and guidelines for prevention, diagnosis and treatment of Diabetes and its associated complications - To closely monitor the morbidity and mortality associate with this disease. - Capacity building at different levels to address different aspects of this disease - To project diabetes as a global health issue and identify the population at risk Efforts to prevent and treat diabetes are essential to achieve the global sustainable development goal target of reducing premature mortality from non communicable diseases by one third by 2030. The community at large and the health care professionals and organizations in particular have a key role to play in highlighting the steps to be taken in this regard through organizing seminars and lectures and making use of the media to effectively communicate their  message to the masses.Globalhealth dayfocusing onDiabetes certainlypromises tobe akeyeventin raising awareness andproposing effective measures supplementing themanagement of this disease ona globalstage.